INCREASING LEARNING ACHIEVEMENT OF PARTS OF SPEECH THROUGH THE USE OF CROWN ACADEMY OF ENGLISH FIRST YEAR AIRCRAFT ENGINEERING CADETS AT AVIATION POLYTECHNIC OF SURABAYA - fatmawati fatmawati; laila rochmawati; meita maharani sukma; irma tenta (Jurnal Penelitian)
Parts of Speech is one of the material in the learning curriculum first-year aircraft engineering cadets that often cadets make mistakes when making and using sentences using words about Noun-Pronoun, Verbs, Adjectives, Adverbs, Conjunction, Number, Articles, Preposition. The purpose of this study was to determine the differences in the increase in learning outcomes of English learning cadets in the Part of Speech material before and after using the Crown Academy of English method. The sample of this study is aircraft engineering cadets 4C at the Aviation Polytechnic of Surabaya. This research was conducted in November 2018. Data collection methods in this study were observations, tests, interviews, and field notes. The data analysis technique used is data reduction, data presentation, drawing conclusions, and verification of reflection.